Agility and Resilience in Cement Industry Supply Chains: Investigating Their Roles in Enhancing Financial Performance - Haryanti, Debby Sri; Santosa, Wahyuningsih; Darasih, Ratna; Widowati, Dorina (Golden Ratio of Mapping Idea and Literature Format, 2026)
This study aims to analyze the influence of Supply Chain Management on Financial Performance, with Supply Chain Agility and Resilience as the moderation variables. This study uses a quantitative approach using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method, and involves 200 respondents from cement manufacturing companies in the Bogor area. The analysis showed that only one of the three hypotheses proved significant, namely the direct influence of Supply Chain Management on Financial Performance (significance value p = 0.024). Meanwhile, the Supply Chain Agility variable did not significantly moderate the relationship between Supply Chain Management and Financial Performance (p = 0.482), nor did the combination of Supply Chain Agility and Resilience (p = 0.345). These findings emphasize the importance of optimizing supply chain management practices to improve a company's financial performance. On the other hand, the effectiveness of the moderation of agility and resilience requires stronger support through technology integration, adaptive information systems, and the development of human resources that are responsive to change, especially in the context of the relatively stable cement industry.